A Multimessenger Mass Determination Method for LISA Neutron Star–White Dwarf Binaries - Kaye Jiale Li; Jane SiNan Long; Kinwah Wu; Albert K. H. Kong (The Astrophysical Journal)
Determining the masses of neutron stars (NSs) accurately improves our understanding of the NS interior and complicated binary evolution. However, the masses of the systems are degenerate with the orbital inclination angle when using solely gravitational waves (GWs) or electromagnetic measurements, especially for face-on binaries. Taking advantage of both GWs and optical observations for LISA NS–white dwarf (WD) binaries, we propose a mass determination method utilising multimessenger observational information. By combining the binary mass function obtained from optical observations and a GW mass function, which we introduce, derived from GW observations, we demonstrate how we can set improved constraints on the NS mass and break the degeneracy in the mass and viewing inclination determination. We further comment on the universal relation of the error bar of the GW mass function versus the GW signal-to-noise ratio and propose a simple method for estimating the capability of using GW observations for mass determination with LISA. We show that for ultracompact NS–WD binaries within our Galaxy, the mass of the NS can be constrained to within an accuracy of  ±0.2 M _⊙ with the proposed method.